HUBUNGAN ANTARA INTENSITAS KOMUNIKASI DENGAN KOMITMEN PERNIKAHAN PADA PASANGAN LONG DISTANCE MARRIAGE (LDM) - Azza Afirul Akbar (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
Couples who have a long-distance relationship certainly have little chance to meet their partner in person considering that the distance is far and rare or even haven't seen each other in a long time. So it takes the intensity of communication so that the commitment to marriage is always maintained. The purpose of this study was to determine the relationship between communication intensity and marital commitment in couples who are in a relationship. The method used in this study is to use correlational quantitative methods with simple regression analysis techniques. The results of this study indicate that the significance value is p=0.000 (p<0.05) which indicates that the higher the intensity of communication, the higher the commitment to marriage. Conversely, the lower the intensity of communication, the lower the commitment to marriage.